Development of ribbon ion beam source and transport system for industrial applications - Masunov, E.S.; Polozov, S.M.; Kulevoy, T.V.; Kuibeda, R.P.; Pershin, V.I.; Petrenko, S.V.; Seleznev, D.N.; Shamailov, I.M.; Sitnikov, A.L. (Вопросы атомной науки и техники, 2008)
The design of ribbon ion source and transport system is discussed in this paper. This system is created at ITEP for ion beam implantation in semiconductor technology. The Bernas type ion sources are used for ribbon ion beam production. The periodic system of electrostatic lenses is proposed for intensive ion beam transport. The results of implanter component development are observing.